Antioxidant Activity of Graphene Quantum Dots Prepared in Different Electrolyte Environments - Zhao, Lin (Nanomaterials (Basel), 2019)
Antioxidants can reduce or inhibit damage such as oxidative decay caused by elevated levels of free radicals. Therefore, pursuing antioxidants with excellent properties has attracted more and more attention. Graphene quantum dots (GQDs) are considered a promising material because of their good free radical scavenging activity, low toxicity, and excellent water solubility. However, their scavenging efficiency, antioxidant mechanism, and effective control methods need to be improved. Herein, in order to further reveal the antioxidant mechanism of GQDs, the role of electrolytes in improving the antioxidant activity of GQDs is explored. In addition, 1,1-diphenyl-2-picrazine (DPPH∙), hydroxyl (∙OH), and superoxide (∙O(2)(−)) free radicals are used to evaluate the antioxidant activity of the as-prepared GQDs. Combined with transmission electron microscopy, Fourier-transform infrared spectroscopy, Raman spectroscopy, and cyclic volt–ampere characteristic curves, the effects of an electrolytic environment on the surface functional groups, charge transfer capability, and defect states of GQDs are obtained. The antioxidant mechanism of GQDs and how to improve their antioxidant activity are further elucidated.